Declining harbour seal abundance in a previously recovering meta-population - Daire Carroll; Markus P. Ahola; Anja M. Carlsson; Anders Galatius; Kjell T. Nilssen; Tero Härkönen; Karin C. Harding (PLoS ONE, 2025)
We present evidence that the abundance of harbour seals in the Kattegat-Skagerrak is in decline. Until recently, the Kattegat-Skagerrak harbour seal population has grown exponentially as it has recovered from historic over-hunting and two mass mortality events. This has provided an important case study for the influence of environmental factors on population growth. Over recent years, deteriorating average body condition and reduced pup counts in certain colonies have indicated that the population is under stress. At the same time, there has been an increase in hunting in the region which may compound existing environmental stressors. To determine trends in harbour seal abundance, we compile aerial survey data for the Kattegat-Skagerrak and South-Western Baltic Sea (S.W. Baltic) populations between the years 2003 and 2023. With parametric modelling, we find that a logistic growth model is the best fit for aerial survey data from the Kattegat-Skagerrak population, while an exponential growth model is the best fit for data from the smaller S.W. Baltic population. We determine trends by fitting non-parametric Generalised Additive Models (GAMs) to aerial survey data and calculating their first derivative. In the Kattegat-Skagerrak, we estimate an annual decline of – 408 individuals (SE = 242, CI95% = [- 882, 67]) at the end of the survey period. This decline represents approximately 3.3% of the estimated mean count in 2023. Rate of change remained positive in the separate S.W. Baltic population throughout the survey period at an estimated annual increase of 54 individuals (SE = 23, CI95% = [9,99]), representing approximately 3.9% of mean counts in 2023. We find that the final rate of change was zero or below zero in eleven out of twelve subregions (representing individual colonies) in the Kattegat-Skagerrak. Declining counts in the Kattegat-Skagerrak since the mid-2010s may be influenced by changes in haul-out behaviour as a result of increased population density or vessel traffic. Despite this, declines likely reflect real changes in seal abundance. Changes in abundance may be the result of well documented environmental degradation affecting prey availability and causing regionally lowered birth rates.